Sleep and behavioral problems in Down syndrome: differences between school age and adolescence - Fucà, Elisa; Costanzo, Floriana; Celestini, Laura; Galassi, Paolo; Villani, Alberto; Valentini, Diletta; Vicari, Stefano (Frontiers in Psychiatry, 2023)
Background Individuals with Down syndrome (DS) are at risk of developing sleep problems. In spite of the well-established knowledge on the presence of sleep difficulties in DS individuals and the associated emotional and behavioral problems, less is known about the possible differences in the kind of associations between sleep and emotional/behavioral problems across different age ranges. Methods In this retrospective study, we included 289 participants with DS aged 6–18 years with the aims to explore differences in the distribution of sleep problems between specific age groups (school age vs. adolescence) and to identify specific age-based associations between sleep problems and emotional/behavioral problems. Results Some differences in the distribution of sleep problems have emerged between age groups. Moreover, differences in the patterns of association between emotional/behavioral difficulties and sleep problems-in particular, sleep-related breathing difficulties and parasomnias-have been observed. However, sleep-wake transition disorders and excessive daily somnolence appear to be related to emotional and behavioral problems (both internalizing and externalizing), in general, across school age and adolescence. Discussion These results remark the importance of appropriate neuropsychiatric and psychological evaluation taking into account the age-specific needs and features of individuals with DS.